KETENTUAN PENANGGUHAN EKSEKUSI HAK TANGGUNGAN OLEH KREDITUR SEPARATIS AKIBAT ADANYA PUTUSAN PAILIT - Trianna, Komang; Dirksen, A.A. Ngurah Gede (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 02, Februari 2013)
Bankruptcy is one of the process of settlement of debts through the institution of Court of Commerce. With the Treaty of guarantee which is accesoir, that means following the agreement anyway, then the applicable provisions vary for each creditor. The lender is the lender who holds the separatists objects guarantee that execution of guarantee especially the rights of those dependents have no effect against the ruling of the bankruptcy that befell the debtor. The position of creditors separatists are higher than other creditors, namely the preferent creditors having privileges and concurrent creditors. Thus the execution of one of the objects which guarantee rights to dependents by separatist creditors use different rules because it did not affect the verdict issued by the Bankruptcy Court of Commerce.
Keywords: Rights, Creditors, Separatist, Bankruptcy